Psychogenic Status Epilepticus - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
Six (21%) of 29 children admitted to the Columbus Children's Hospital, OH, in a 6-month prospective period, with a diagnosis of convulsive status epilepticus proved to have psychogenic status epilepticus and comorbid affective and anxiety disorders.